Synthesis of chitosan biofilms crosslinked with tripolyphosphate acting as chelating agent in the fixation of silver nanoparticles - Dilarri, Guilherme [UNESP]; Mendes, Carolina Rosai; Martins, Amarildo Otavio (PPUFU - Portal de Periódicos da Universidade Federal de Uberlândia, 2016)
Silver nanoparticles have been incorporated in the various materials, using different complexation agents. The work aims at the incorporation of silver nanoparticles in biofilms of chitosan using as agent crosslinker and complexing sodium tripolyphosphate. We used the method of reduction of silver salts in aqueous medium for synthesis of nanoparticles, determining the through the analysis of their plasmonic band by UV-Vis spectrophotometry. In order to compare the efficiency of tripolyphosphate was used biofilms non-crosslinked and filter paper as material control. The analyses in UV-Vis showed the presence of a single plasmon band centered around 400 nm, which is indicative of nanoparticles with spherical shape. Studies of incorporation of the silver nanoparticles showed the efficiency of tripolyphosphate in fixing, complexing all the silver colloidal solution tested in comparison to others materials, thus proving the efficiency of tripolyphosphate as a chelating agent in the fixation of silver nanoparticles.
Síntese de biofilmes de quitosana reticulados com tripolifosfato atuando como agente quelante na fixação de nanopartículas de prata
Keywords: Adsorption; Chitosan; Polymer; Silver nanoparticles; Tripolyphosphate